"History Is Our Playground": Action and Authenticity in Assassin's Creed: Odyssey. Issue 3 (August 2019) - Politopoulos, Aris; Mol, Angus A. A.; Boom, Krijn H. J.; Ariese, Csilla E.
Overview: Ubisoft's Assassin's Creed series is one the entertainment industry's most popular titles set in the past. With a new game released on an annual basis—each full of distinct historical places, events, and people—the series has unfolded across post-classical history, from the Levant during the Third Crusade to Victorian-era London. The 2017 release of Assassin's Creed: Origins, which entailed a massive reconstruction of Hellenistic Egypt, pushed the series even further back in time. With it, Ubisoft also launched its Discovery Tour, allowing players to explore the game's setting at their leisure and without combat. These trends continued in 2018's Assassin's Creed: Odyssey, set in Greece during the Peloponnesian War. This review discusses the narrative, world, and gameplay of the latest Assassin's Creed within the series more broadly. We provide a critical appraisal of the experience that Odyssey offers and link it to this question: in the Assassin's Creed series, do we engage in meaningful play with the past, or are we simply assassinating our way through history?